OCT Biometry (B-OCT): A New Method for Measuring Ocular Axial Dimensions - Bartosz L. Sikorski; Pawel Suchon (Journal of Ophthalmology)
Purpose. To present a new method of measuring ocular axial dimensions, termed OCT biometry (B-OCT). Design. Observational cross-sectional study and evaluation of new diagnostic technology. Methods. B-OCT was implemented in the spectral domain OCT device for posterior and anterior segment imaging (REVO NX, Optopol Technology). A total of 349 eyes (214 of healthy subjects, 115 of patients with cataract, and 20 with severe macular diseases) were enrolled in the study. The results of B-OCT were compared to swept source OCT-based IOLMaster 700 (Carl Zeiss Meditec). Differences in measurement values between the two biometers were determined using the paired t-test. Agreement was assessed through intraclass correlation coefﬁcients (ICCs) and Bland–Altman plots. Results. B-OCT obtained with REVO NX provides excellent interobserver reproducibility (ICC for: axial length (AXL) = 1.000; central corneal thickness (CCT) = 0.933; anterior chamber depth (ACD) = 0.933; lens thickness (LT) = 0.985) and intraobserver repeatability (ICC for: AXL = 1.000; CCT ≥ 0.994; ACD = 0.998; LT ≥ 0.993). The correlation between measurements made using both devices was outstanding (ICC for: AXL, healthy = 1.000; AXL, cataractous = 1.000; ACD, healthy = 0.998; ACD, cataractous = 0.997; LT, healthy = 0.998; LT, cataractous = 0.997; CCT, healthy = 0.989; CCT, cataractous = 0.979). The mean AXL measurement difference in healthy eyes was −0.001 ± 0.016 mm (the 95% LoA ranged from −0.034 to 0.031); mean ACD difference was 0.000 ± 0.024 mm (95% LoA, −0.047 to 0.047); mean LT difference was −0.002 ± 0.024 mm (95% LoA, −0.050 to 0.046); and mean CCT difference  was −0.8 ± 5.1 μm (95% LoA, −10.81 to 9.26). The mean AXL measurement difference in cataractous eyes was −0.003 ± 0.022 mm (95% LoA, −0.046 to 0.039); mean ACD difference was 0.003 ± 0.029 mm (95% LoA, −0.054 to 0.059); mean LT difference was −0.002 ± 0.025 (95% LoA, −0.051 to 0.048); and mean CCT difference was 2.7 ± 6.4 μm (95% LoA, −9.80 to 15.7). Conclusion. The study shows small, nonsignificant differences between the biometric measurements obtained with REVO NX B-OCT and IOLMaster 700, which is of high significance for IOL power selection. As B-OCT utilizes a conventional OCT device, the measurements of the ocular axial dimensions are combined with high-resolution macular scans for the simultaneous assessment of central retina as a part of screening for macular pathology. The presented method is the first spectral domain OCT-based biometry technique and the only one integrated into a standard OCT device. Thus, it brings novel functionality to OCT technology.